MODEL PEMBELAJARAN COOPERATIVE LEARNING DI SMP NEGERI SE-KECAMATAN PONTIANAK KOTA - Saputra, Raka Dwi; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ The cooperative learning learning model which has been considered difficult for teachers to be able to provide the best contribution when learning physical education, especially cooperative learning models with the existence of the model so that students at the time of learning will be more interesting and uplifting. The method used in the study is quantitative descriptive with survey techniques, namely by describing a percentage level of teacher perceptions in East Pontianak about cooperative learning learning models with the number of research subjects totaling 11 sports teachers and carried out during learning in March 2019. The results showed that the Penjas learning model itself proved a real score of 27.75 maximum score of 155 with a percentage of 52% referring to the good category meaning the teacher understood about cooperative learning learning models for more learning so we can convey that the level of perceptual teacher perceptions of the learning model cooperative learning very good category 183-210 with a percentage of 0%, good 155-182 with a percentage of 26 with a percentage of 52%, less 127-154 with a frequency of 24 percent 48% less categoriesKeywords:Penjas Learning, Perception of Cooperative Learning Model